Exploring the Relationship between Economic Growth and Environmental Sustainability - Winda Anwarya (Journal of Management and Administration Provision, 2022)
This research examines the link between economic development and ecological sustainability, paying special attention to the detrimental effects that rapid economic expansion could have on the natural world. We used descriptive statistics, trend analysis, correlation analysis, regression analysis, hypothesis testing, sensitivity analysis, and robustness checks on cross-sectional data from a selection of countries to investigate the moderating role of environmental protection expenditure on the relationship between GDP per capita and carbon emissions per capita. We find that spending on environmental safeguards moderates the correlation between GDP per individual and carbon emissions. These results stress the significance of supporting environmentally sustainable development practices and increasing spending on environmental protection, especially in countries experiencing rapid economic expansion. For those working to support sustainable development and lessen the environmental costs of economic growth, our research offers crucial new information.